A method for producing lithium hexafluorophosphate
Patent Information
- Application Number
- CN202611260739.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]这种路线存在以下固有缺陷:深冷条件需要大量制冷能耗,据报道5000吨级装置需配备20至40台结晶釜,制冷系统投资和运行成本巨大氟化氢在低温下粘度急剧增大,-40℃时粘度约为0℃时的3倍以上,传质效率极差,导致晶体生长不均匀,LiF杂质被生长的六氟磷酸锂晶体包覆而难以脱除;由于粘度高、传质差,结晶时间长达10至48h,生产效率极低;深冷条件下釜壁与溶液之间存在巨大温差,导致严重的釜壁结疤问题
[0029]1、 本发明采用中等温度下的受控减压蒸发结晶取代传统的深冷冷却结晶,结晶温度由-30至-50℃提高至-5至5℃,制冷能耗降低60%以上;蒸发出的氟化氢在-25℃左右即可冷凝回收,无需深冷至-50℃,大幅降低了冷媒系统的投资和运行成本。
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery electrolyte production technology, specifically to a method for preparing lithium hexafluorophosphate. Background Technology
[0002] Lithium hexafluorophosphate (LiPF6) is currently the most widely used electrolyte lithium salt in lithium-ion battery electrolytes, accounting for approximately 43% of the total cost of electrolytes. Lithium hexafluorophosphate exhibits moderate ion transference number and dissociation constant in organic carbonate solvents, good antioxidant capacity and electrochemical stability, as well as excellent passivation effect on aluminum foil, making it the most important electrolyte lithium salt for the foreseeable future.
[0003] The preparation methods of lithium hexafluorophosphate mainly include three types: gas-solid method, hydrogen fluoride solvent method, and organic solvent method. Among them, the hydrogen fluoride solvent method is the most widely used process route in industrial applications. Its principle is to dissolve lithium fluoride in anhydrous hydrogen fluoride to form a solution, and then introduce phosphorus pentafluoride gas to react and generate lithium hexafluorophosphate. The product is then obtained through crystallization, separation, and drying. This method has a fast reaction rate and high conversion rate, making it suitable for large-scale production.
[0004] However, the hydrogen fluoride solvent method faces severe challenges in the crystallization process. The method disclosed in patent CN102910612A uses cryogenic conditions below -40°C for cooling and crystallization, which takes more than 6 hours. The entire process is energy-intensive and has a long operation cycle. Patent CN115744938B discloses a method for rapidly crystallizing and preparing spherical lithium hexafluorophosphate crystals in the presence of a carbonate inducer, but its crystallization temperature still needs to be lowered to below -30°C. Patent CN117917380A discloses a method for controlling the packing density and introducing phosphorus pentafluoride gas to improve the conversion efficiency of lithium fluoride, but its crystallization still depends on cryogenic conditions.
[0005] Existing technologies also report methods for accelerating crystallization rates through ultrasonic induction and dynamic crystallization methods combining gradient cooling with ultrasonic induction. However, these methods are highly dependent on equipment, difficult to scale up industrially, and still require crystallization times of more than 10 hours, and still need to be operated under cryogenic conditions below -30°C.
[0006] The aforementioned existing technologies all employ a cooling crystallization route, which involves reducing the solubility of lithium hexafluorophosphate in hydrogen fluoride by cooling the solution to extremely low temperatures, thereby driving crystallization.
[0007] This approach has the following inherent drawbacks: cryogenic conditions require a large amount of refrigeration energy; it has been reported that a 5,000-ton-class plant requires 20 to 40 crystallization reactors, resulting in huge investment and operating costs for the refrigeration system. The viscosity of hydrogen fluoride increases dramatically at low temperatures, reaching more than three times that at 0°C at -40°C, leading to extremely poor mass transfer efficiency and uneven crystal growth. LiF impurities are encapsulated by the grown lithium hexafluorophosphate crystals and are difficult to remove. Due to the high viscosity and poor mass transfer, the crystallization time is as long as 10 to 48 hours, resulting in extremely low production efficiency. Under cryogenic conditions, there is a huge temperature difference between the reactor wall and the solution, leading to severe scaling problems on the reactor wall.
[0008] In theory, evaporation crystallization is a feasible alternative to cooling crystallization; however, in the field of lithium hexafluorophosphate, evaporation crystallization is generally considered an infeasible solution. The background technology of patent CN114713154B clearly points out that the continuous process of evaporation concentration crystallization has high energy consumption, thus negating the feasibility of this route. The reason is that traditional evaporation crystallization requires heating the solution to a high temperature to evaporate the hydrogen fluoride, and then condensing and recovering the evaporated hydrogen fluoride. The two temperature jumps, one heating and one cryogenic cooling, result in a total energy consumption that is far greater than that of direct cryogenic crystallization. Therefore, the evaporation crystallization route has formed a technical bias in this field: evaporation crystallization is more energy-intensive and less practical than cooling crystallization, and should not be adopted.
[0009] In addition, lithium hexafluorophosphate crystals produced by traditional processes generally have problems such as LiF residue and high HF acidity; LiF is coated inside the lithium hexafluorophosphate crystals and cannot be removed by conventional washing.
[0010] Existing technologies disclose a method for purification by passing a mixture of phosphorus pentafluoride and hydrogen chloride gas at 100 to 160°C. This method utilizes the reaction of phosphorus pentafluoride with residual lithium fluoride and fluorophosphate impurities to convert lithium hexafluorophosphate. However, lithium hexafluorophosphate is prone to thermal decomposition at high temperatures, which leads to a decrease in product purity and yield.
[0011] Therefore, there is an urgent need to develop a method for preparing high-quality lithium hexafluorophosphate that can reduce crystallization energy consumption, shorten crystallization time, and reduce LiF impurity coating and HF residue. Summary of the Invention
[0012] The primary objective of this invention is to provide a method for preparing lithium hexafluorophosphate.
[0013] A further objective of this invention is to provide a method for preparing lithium hexafluorophosphate, comprising the following steps:
[0014] Step 1: Dissolve lithium fluoride in anhydrous hydrogen fluoride, and then pass phosphorus pentafluoride gas through it to react and obtain a hydrogen fluoride solution of lithium hexafluorophosphate.
[0015] Step 2: Transfer the lithium hexafluorophosphate hydrogen fluoride solution obtained in Step 1 to a crystallization vessel. Under stirring conditions, slowly reduce the system pressure from atmospheric pressure to 15 to 30 kPa absolute pressure at a rate of 0.5 to 3 kPa / min, while maintaining the system temperature at -5 to 5°C, so that the hydrogen fluoride evaporates in a controlled manner and lithium hexafluorophosphate crystallizes out due to the increased concentration, thus obtaining a slurry containing lithium hexafluorophosphate crystals.
[0016] Step 3: Perform solid-liquid separation on the crystal slurry obtained in Step 2, remove the mother liquor, and obtain wet lithium hexafluorophosphate crystals;
[0017] Step 4: Place the wet lithium hexafluorophosphate crystals obtained in Step 3 into a purification reactor, introduce phosphorus pentafluoride gas at 10 to 25°C, maintain the system pressure at 0.05 to 0.2 MPa gauge pressure, and treat for 1 to 3 hours to allow phosphorus pentafluoride to react with the residual lithium fluoride in the wet crystals to generate lithium hexafluorophosphate, while removing hydrogen fluoride adsorbed on the crystal surface and in the gaps.
[0018] Step 5: The lithium hexafluorophosphate crystals processed in Step 4 are vacuum dried under nitrogen protection to obtain the lithium hexafluorophosphate product.
[0019] Preferably, in step one, the mass concentration of lithium fluoride in anhydrous hydrogen fluoride is 3.0 to 4.5%, the molar ratio of phosphorus pentafluoride to lithium fluoride is 1.01 to 1.05:1, the reaction temperature is -15 to -5°C, and the reaction time is 3 to 5 hours.
[0020] Preferably, in step two, the slow decompression process is divided into three stages: the first stage reduces the pressure from atmospheric pressure to 15 to 30 kPa at a rate of 0.5 to 3 kPa / min, taking 0.5 to 3.0 h; the second stage maintains the pressure at 15 to 30 kPa and continues to evaporate hydrogen fluoride to allow crystallization to continue, taking 2 to 4 h; the third stage reduces the pressure from 15 to 30 kPa to 5 to 12 kPa at a rate of 0.3 to 1 kPa / min, while simultaneously reducing the temperature to -10 to -5 °C, taking 1 to 2 h.
[0021] Preferably, in step two, the system temperature in the first and second stages is -3 to 3°C, and the system temperature in the third stage is -8 to -5°C.
[0022] Preferably, in step two, the stirring speed is 50 to 150 rpm, and the evaporated hydrogen fluoride is condensed and recovered by a condenser at -30 to -20°C and recycled.
[0023] Preferably, in step three, solid-liquid separation is performed using nitrogen pressurized filtration with a nitrogen pressure of 0.1 to 0.3 MPa gauge pressure, and the separated mother liquor is recycled back to step one for reuse.
[0024] Preferably, in step four, the flow rate of phosphorus pentafluoride gas is 0.5 to 2.0 L / min per kilogram of wet lithium hexafluorophosphate crystals.
[0025] Preferably, in step five, the vacuum drying temperature is 40 to 55°C, the absolute pressure is 5 to 15 kPa, the nitrogen purging flow rate is 0.5 to 2.0 L / min per kilogram of lithium hexafluorophosphate, and the drying time is 4 to 8 hours.
[0026] Preferably, in step one, the purity of lithium fluoride is ≥99.95%, the D50 is 5 to 15 μm, and the moisture content is ≤10 ppm; the purity of anhydrous hydrogen fluoride is ≥99.99%, and the moisture content is ≤5 ppm.
[0027] Preferably, after step four is completed, the purification reactor is purged with high-purity nitrogen to replace the residual phosphorus pentafluoride gas, with the nitrogen purity ≥99.999% and the purging time being 10 to 30 minutes.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] 1. This invention uses controlled reduced pressure evaporation crystallization at a moderate temperature to replace traditional cryogenic cooling crystallization. The crystallization temperature is increased from -30 to -50°C to -5 to 5°C, reducing refrigeration energy consumption by more than 60%. The evaporated hydrogen fluoride can be condensed and recovered at around -25°C, eliminating the need for cryogenic cooling to -50°C, which significantly reduces the investment and operating costs of the refrigerant system.
[0030] 2. The present invention has low viscosity and high mass transfer efficiency of hydrogen fluoride at medium temperature, and LiF impurities can diffuse fully at the crystal growth interface without being coated, which significantly reduces the content of insoluble matter in the product.
[0031] 3. The crystallization time of this invention is shortened from 10 to 48 hours in the traditional process to 4 to 7 hours, which greatly improves production efficiency; the number of crystallization kettles required for the same production capacity is reduced by more than 50%, and equipment investment is significantly reduced.
[0032] 4. This invention uses low-temperature PF5 gas-phase purification at 10 to 25°C, avoiding the risk of thermal decomposition of lithium hexafluorophosphate caused by traditional high-temperature purification at 100 to 160°C. The product purity reaches over 99.94%, and the free acid content is less than 16 ppm. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] This invention achieves the crystallization of lithium hexafluorophosphate by controlled vacuum evaporation of hydrogen fluoride at a moderate temperature, combined with low-temperature PF5 gas-phase purification to obtain a high-purity product.
[0035] The existing technology believes that the fundamental reason why evaporation crystallization is not feasible is that it refers to the high-temperature evaporation mode, that is, first heating the solution to a high temperature to evaporate the hydrogen fluoride, and then subjecting the evaporated hydrogen fluoride to deep cryogenic condensation. The two large temperature jumps result in a total energy consumption that is far greater than that of deep cryogenic crystallization.
[0036] However, this invention has found that the saturated vapor pressure of hydrogen fluoride at 0°C is approximately 50 kPa, and even after considering the Raoult correction due to the dissolution of lithium hexafluorophosphate, it is still not less than 45 kPa. If the system pressure is reduced to 15 to 30 kPa at around 0°C, the system pressure is lower than the equilibrium vapor pressure of hydrogen fluoride, and hydrogen fluoride can continue to evaporate without heating. The evaporation process absorbs the latent heat of vaporization, causing the solution to cool down naturally. Only a small amount of heat needs to be added through the jacket to maintain the temperature to achieve isothermal evaporation. The evaporated hydrogen fluoride can be liquefied and recovered in a condenser at around -25°C, without the need for deep cooling to -50°C.
[0037] Therefore, the reduced pressure evaporation crystallization of the present invention has a much narrower overall temperature range than the cryogenic crystallization route, and the refrigeration load is significantly reduced.
[0038] More importantly, at moderate temperatures of -5 to 5°C, the viscosity of hydrogen fluoride is much lower than that at -30 to -50°C, resulting in a significant improvement in mass transfer efficiency.
[0039] The growth rate of lithium hexafluorophosphate crystals is more uniform, the crystal morphology is regular and the particle size distribution is concentrated, which reduces the probability of LiF being coated inside the crystal; LiF impurities have sufficient diffusion ability in solution, which can establish a concentration gradient near the crystal growth interface, avoiding the problem of LiF being enriched and coated at the growth interface.
[0040] These two effects are impossible to achieve in cryogenic crystallization due to the impeded mass transfer caused by high viscosity.
[0041] Furthermore, the controlled decompression rate of 0.5 to 3 kPa / min used in this invention is a key parameter.
[0042] Within this rate range, the hydrogen fluoride evaporation rate is moderate, the supersaturation of lithium hexafluorophosphate in the solution is established slowly, and the crystallization driving force is mild and continuous, which is conducive to the orderly growth of crystal nuclei on the surface of existing crystals rather than explosive spontaneous nucleation.
[0043] When the decompression rate is below 0.5 kPa / min, the supersaturation is established too slowly, the crystallization cycle is too long, and it loses its practical significance. When the decompression rate is above 3 kPa / min, the hydrogen fluoride evaporates too quickly, the local supersaturation of the solution increases sharply, resulting in explosive nucleation and the formation of a large number of fine crystals. Moreover, LiF does not have time to diffuse and is coated, and the crystal quality decreases instead.
[0044] In the purification stage after crystallization, this invention uses low-temperature PF5 gas-phase purification at 10 to 25°C, instead of the high-temperature purification at 100 to 160°C used in traditional processes. The feasibility of low-temperature purification is based on the following principle: a small amount of hydrogen fluoride liquid film still adheres to the surface and gaps of the wet lithium hexafluorophosphate crystals after crystallization. PF5 gas has sufficient solubility in this liquid film and can react with the residual LiF in a quasi-liquid phase reaction. Although the reaction rate of PF5 and LiF is lower at 10 to 25°C than at high temperatures, the LiF content in the crystals obtained by evaporation and crystallization in this invention has been greatly reduced, leaving only a small amount of residual LiF on the surface. A processing time of 1 to 3 hours at low temperature is sufficient to fully convert it.
[0045] Meanwhile, the low temperature ensures that lithium hexafluorophosphate will not undergo thermal decomposition, and the physical scouring effect of the PF5 gas flow passing through the intercrystalline gaps can also effectively remove adsorbed HF.
[0046] This low-temperature PF5 purification is an adaptation of the medium-temperature evaporation crystallization process of the present invention: it is precisely because evaporation crystallization avoids deep cooling conditions that the LiF in the resulting crystal is not buried deep inside the crystal but is on the surface or in the shallow layer, so that low-temperature PF5 is sufficient to complete the purification.
[0047] Raw material source:
[0048] Anhydrous hydrogen fluoride: purity ≥99.99%, moisture content ≤5ppm, supplier: Do-Fluoride New Materials Co., Ltd.
[0049] Lithium fluoride: purity ≥99.95%, D50 8 to 12 μm, porous agglomerated particles, the primary particle size is much smaller than the agglomerate size characterized by D50, specific surface area ≥5 m² 2 / g, moisture content ≤10ppm, supplier: Do-Fluoride New Materials Co., Ltd.
[0050] Phosphorus pentachloride: purity ≥99.9%, moisture content ≤10ppm, supplier: Jiangsu Meilan Chemical Co., Ltd.
[0051] High-purity nitrogen: purity ≥ 99.999%, moisture content ≤ 1 ppm, oxygen content ≤ 1 ppm, supplier: Wuhan Iron and Steel Group Gas Co., Ltd.
[0052] Phosphorus pentafluoride gas: It is prepared by reacting phosphorus pentachloride with excess anhydrous hydrogen fluoride in a PF5 generator at 60 to 80°C. After separating hydrogen chloride and excess hydrogen fluoride, PF5 gas with a purity of ≥99.5% is obtained.
[0053] Example 1:
[0054] Raw material formula:
[0055] 500g of anhydrous hydrogen fluoride, 19.2g of lithium fluoride, and 96.0g of phosphorus pentafluoride gas based on a PF5 to LiF molar ratio of 1.03:1.
[0056] Preparation process:
[0057] Step 1, Lithium hexafluorophosphate synthesis: 500g of anhydrous hydrogen fluoride was added to a 1L 316L stainless steel reactor. The jacket cooling system was turned on to lower the temperature to -15℃. 19.2g of lithium fluoride was added under stirring and stirred for 30min to dissolve. The reactor temperature was controlled at -10℃, and the mass concentration of LiF in HF was 3.7%. Phosphorus pentafluoride gas was introduced into the reactor at a flow rate of 200mL / min. The molar ratio of PF5 to LiF was 1.03:1. The reaction temperature was controlled at -10℃, the reaction pressure was 0.1MPa gauge pressure, and the stirring speed was 250rpm. After the feeding was completed, the reactor was kept at -10℃ for 3h to obtain a hydrogen fluoride solution of lithium hexafluorophosphate.
[0058] Step 2, controlled vacuum evaporation crystallization: Transfer the solution obtained in Step 1 to a 1L crystallization vessel equipped with a condenser, a vacuum system and a mechanical stirrer; turn on the stirrer at 80 rpm and maintain the vessel temperature at 0℃.
[0059] The vacuum system was started, and the system pressure was slowly reduced from 101 kPa to 22 kPa at a rate of 1.5 kPa / min, which took about 53 minutes.
[0060] Then, maintaining a pressure of 22 kPa, the hydrogen fluoride was evaporated and crystallization continued for 3.25 hours.
[0061] Finally, the pressure was reduced from 22 kPa to 8 kPa at a rate of 0.5 kPa / min, while the temperature was reduced to -5 °C and maintained for 1 hour.
[0062] The hydrogen fluoride evaporated throughout the process was condensed and recovered at -25°C using a condenser; the total crystallization time was 5.6 hours, yielding a slurry containing lithium hexafluorophosphate crystals.
[0063] Step 3, solid-liquid separation: Under nitrogen protection, the crystal slurry is transferred to a filter and filtered under pressure with nitrogen at a gauge pressure of 0.2 MPa. The separated mother liquor is recycled to Step 1 for reuse, yielding wet lithium hexafluorophosphate crystals.
[0064] Step 4, PF5 gas phase purification: Place the wet crystals in the purification reactor, introduce phosphorus pentafluoride gas, control the temperature at 15℃, the system pressure at 0.1MPa gauge pressure, the PF5 flow rate at 1.0L / min per kilogram of wet crystals, and treat for 2 hours; after treatment, purge the purification reactor with high-purity nitrogen for 20 minutes to replace the residual PF5.
[0065] Step 5, Drying: Transfer the purified lithium hexafluorophosphate crystals to a vacuum dryer and dry them at 45°C and 8 kPa absolute pressure for 6 hours under nitrogen purging flow rate of 1.0 L / min per kilogram of lithium hexafluorophosphate to obtain the lithium hexafluorophosphate product.
[0066] In this embodiment, the lithium hexafluorophosphate product has a purity of 99.96%, a free acid content of 12.3 ppm, an insoluble matter content of 137 ppm, a moisture content of 5.8 ppm, a D50 of 155 μm, and a yield of 91.2%.
[0067] Example 2:
[0068] Raw material formula:
[0069] 500g of anhydrous hydrogen fluoride, 21.0g of lithium fluoride, and 107.0g of phosphorus pentafluoride gas based on a PF5 to LiF molar ratio of 1.05:1.
[0070] Preparation process:
[0071] Step 1, Lithium hexafluorophosphate synthesis: Same as Example 1, except that the mass concentration of LiF in HF is 4.0%, the molar ratio of PF5 to LiF is 1.05:1, and the reaction temperature is -8℃.
[0072] Step 2, controlled vacuum evaporation crystallization: the equipment and materials are the same as in Example 1, except that the vacuum rate is 2.5 kPa / min. In the first stage, the pressure is reduced from 101 kPa to 18 kPa, which takes about 33 minutes. In the second stage, the pressure is maintained at 18 kPa for 2.7 hours. In the third stage, the pressure is reduced from 18 kPa to 6 kPa at a rate of 0.8 kPa / min, and the temperature is reduced to -8°C for 1 hour.
[0073] Total crystallization time: 4.5 hours.
[0074] Steps three through five are the same as in Example 1.
[0075] In this embodiment, the lithium hexafluorophosphate product has a purity of 99.97%, a free acid content of 9.5 ppm, an insoluble matter content of 105 ppm, a moisture content of 5.2 ppm, a D50 of 138 μm, and a yield of 92.6%.
[0076] Example 3:
[0077] Raw material formula:
[0078] Same as Example 1.
[0079] Preparation process:
[0080] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0081] Step 2, controlled vacuum evaporation crystallization: the equipment and materials are the same as in Example 1, except that the crystallization temperature is -3℃. In the first stage, the vacuum rate is reduced from 101kPa to 25kPa at 1.0kPa / min. In the second stage, the pressure is maintained at 25kPa for 2.7h. In the third stage, the pressure is reduced from 25kPa to 10kPa at 0.5kPa / min, and the temperature is reduced to -5℃ for 1.5h.
[0082] Total crystallization time: 6.0 h.
[0083] Steps three through five are the same as in Example 1.
[0084] In this embodiment, the lithium hexafluorophosphate product has a purity of 99.94%, a free acid content of 15.1 ppm, an insoluble matter content of 168 ppm, a moisture content of 7.3 ppm, a D50 of 172 μm, and a yield of 89.8%.
[0085] Example 4:
[0086] Raw material formula:
[0087] Same as Example 1.
[0088] Preparation process:
[0089] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0090] Step 2, controlled reduced pressure evaporation crystallization: same as in Example 1.
[0091] Step 3, solid-liquid separation: same as in Example 1.
[0092] Step 4, PF5 gas phase purification: The difference is that the purification temperature is 20℃, the system pressure is 0.15MPa gauge pressure, the PF5 flow rate is 1.5L / min per kilogram of wet crystals, and the treatment time is 1.5h.
[0093] Step 5, Drying: Same as in Example 1.
[0094] In this embodiment, the lithium hexafluorophosphate product has a purity of 99.96%, a free acid content of 12.8 ppm, an insoluble matter content of 143 ppm, a moisture content of 6.1 ppm, a D50 of 148 μm, and a yield of 91.8%.
[0095] Example 5:
[0096] Raw material formula:
[0097] 500g of anhydrous hydrogen fluoride, 19.2g of lithium fluoride, and 96.0g of phosphorus pentafluoride gas based on a PF5 to LiF molar ratio of 1.03:1.
[0098] Preparation process:
[0099] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0100] Step 2, controlled vacuum evaporation crystallization: the vacuum rate is 2.0 kPa / min. In the first stage, the pressure is reduced from 101 kPa to 18 kPa, which takes about 42 min and is maintained at 2℃. In the second stage, the pressure is maintained at 18 kPa for 3.0 h and the temperature is 2℃. In the third stage, the pressure is reduced from 18 kPa to 7 kPa at a rate of 0.7 kPa / min and the temperature is reduced to -7℃ for 1 h.
[0101] Total crystallization time: 5.0 h.
[0102] Step 3, solid-liquid separation: same as in Example 1.
[0103] Step 4, PF5 gas phase purification: purification temperature 18℃, system pressure 0.12MPa gauge pressure, PF5 flow rate 1.2L / min per kilogram of wet crystals, treatment for 2 hours.
[0104] Step 5, Drying: 50℃, absolute pressure 6kPa, nitrogen purging 1.0L / min per kilogram of lithium hexafluorophosphate, dry for 5h.
[0105] In this embodiment, the lithium hexafluorophosphate product has a purity of 99.97%, a free acid content of 10.1 ppm, an insoluble matter content of 95 ppm, a moisture content of 5.4 ppm, a D50 of 158 μm, and a yield of 92.1%.
[0106] Comparative Example 1:
[0107] Raw material formula:
[0108] Same as Example 1.
[0109] Preparation process:
[0110] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0111] Step 2, cryogenic crystallization: Transfer the solution obtained in Step 1 to a 1L crystallization vessel, turn on the jacket cooling, and cool from 0℃ to -40℃ at a rate of 2℃ / h, and hold at -40℃ for 8 hours. The total crystallization time is 28 hours.
[0112] Step 3, solid-liquid separation: same as in Example 1.
[0113] Step four: Do not perform PF5 gas phase purification.
[0114] Step 5, Drying: Same as in Example 1.
[0115] The comparative example of lithium hexafluorophosphate product has a purity of 99.82%, a free acid content of 85.7 ppm, an insoluble matter content of 1082 ppm, a moisture content of 16.3 ppm, a D50 of 248 μm, and a yield of 78.1%.
[0116] Comparative Example 2:
[0117] Raw material formula:
[0118] Same as Example 1.
[0119] Preparation process:
[0120] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0121] Step 2, reduced pressure evaporation crystallization but with the decompression rate below the critical range: Transfer the solution to the crystallization vessel and slowly reduce the pressure from 101 kPa to 22 kPa at a rate of 0.2 kPa / min, maintain at 0°C, then maintain at 22 kPa for 4.2 h, and then reduce to 8 kPa for 2 h.
[0122] Total crystallization time: 14 hours.
[0123] Steps three through five are the same as in Example 1.
[0124] The comparative example of lithium hexafluorophosphate product has a purity of 99.88%, a free acid content of 35.2 ppm, an insoluble matter content of 462 ppm, a moisture content of 10.5 ppm, a D50 of 185 μm, and a yield of 82.3%.
[0125] Comparative Example 3:
[0126] Raw material formula:
[0127] Same as Example 1.
[0128] Preparation process:
[0129] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0130] Step 2, reduced pressure evaporation crystallization but with a decompression rate higher than the critical range: Transfer the solution to a crystallization vessel and rapidly reduce the pressure from 101 kPa to 20 kPa at a rate of 5 kPa / min, while maintaining the temperature at 0°C.
[0131] During the decompression process, hydrogen fluoride boils violently, producing a large amount of foam and fine crystals.
[0132] Maintain 20 kPa for 3.2 hours.
[0133] Steps three through five are the same as in Example 1.
[0134] The comparative example of lithium hexafluorophosphate product has a purity of 99.84%, a free acid content of 53.8 ppm, an insoluble matter content of 645 ppm, a moisture content of 12.7 ppm, a D50 of 42 μm, and a yield of 79.8%.
[0135] Comparative Example 4:
[0136] Raw material formula:
[0137] Same as Example 1.
[0138] Preparation process:
[0139] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0140] Step 2, cryogenic cooling crystallization: Same as Comparative Example 1, cool down to -40℃ at 2℃ / h and hold for 8h.
[0141] Total crystallization time: 28 hours.
[0142] Step 3, solid-liquid separation: same as in Example 1.
[0143] Step 4, PF5 gas phase purification: purification temperature 15℃, system pressure 0.1MPa gauge pressure, PF5 flow rate 1.0L / min per kilogram of wet crystals, treatment for 2 hours, conditions are the same as in Example 1.
[0144] Step 5, Drying: Same as in Example 1.
[0145] The lithium hexafluorophosphate product in this comparative example has a purity of 99.91%, a free acid content of 27.4 ppm, an insoluble matter content of 308 ppm, a moisture content of 9.2 ppm, a D50 of 228 μm, and a yield of 80.6%.
[0146] Comparative Example 5:
[0147] Raw material formula:
[0148] Same as Example 1.
[0149] Preparation process:
[0150] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0151] Step 2, cryogenic cooling crystallization: Same as Comparative Example 1, total crystallization time 28h.
[0152] Step 3, solid-liquid separation: same as in Example 1.
[0153] Step 4, high-temperature PF5 purification: purification temperature 120℃, system pressure 0.05MPa gauge pressure, introduce a mixed gas of phosphorus pentafluoride and hydrogen chloride produced by the reaction of phosphorus pentachloride and anhydrous hydrogen fluoride, and treat for 7h.
[0154] Step 5, Drying: Same as in Example 1.
[0155] The comparative example of lithium hexafluorophosphate product has a purity of 99.89%, a free acid content of 22.6 ppm, an insoluble matter content of 342 ppm, a moisture content of 11.8 ppm, a D50 of 215 μm, and a yield of 78.5%.
[0156] Comparative Example 6:
[0157] Raw material formula:
[0158] Same as Example 1.
[0159] Preparation process:
[0160] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0161] Step 2, rapid depressurization evaporation crystallization: Transfer the solution to the crystallization vessel and rapidly reduce the pressure from 101 kPa to 20 kPa at a rate of 10 kPa / min, while maintaining the temperature at 0°C.
[0162] Hydrogen fluoride evaporated rapidly, the solution bubbled violently, and a large number of crystals and scales appeared on the walls of the vessel.
[0163] Maintain 20 kPa for 2.9 hours.
[0164] Step 3, solid-liquid separation: same as in Example 1.
[0165] Step 4, PF5 gas phase purification: Same as in Example 1, 15℃, 0.1MPa gauge pressure, 2h.
[0166] Step 5, Drying: Same as in Example 1.
[0167] This comparative example combines vacuum evaporation with PF5 purification but does not use a controlled vacuum rate. The results show that rapid evaporation leads to extremely poor crystal quality, and PF5 purification cannot compensate for the LiF coating caused during the crystallization stage.
[0168] The comparative example of lithium hexafluorophosphate product has a purity of 99.85%, a free acid content of 48.3 ppm, an insoluble matter content of 512 ppm, a moisture content of 11.5 ppm, a D50 of 58 μm, and a yield of 81.0%.
[0169] Comparative Example 7:
[0170] Raw material formula:
[0171] Same as Example 1.
[0172] Preparation process:
[0173] Step 1, Lithium hexafluorophosphate synthesis: Same as in Example 1.
[0174] Step 2, Ultrasonic-assisted cryogenic cooling crystallization: Transfer the solution to a crystallization vessel equipped with an ultrasonic probe, cool it to -20°C at 4°C / h, apply 200W, 25kHz ultrasound to induce nucleation for 30min, continue cooling to -40°C at 4°C / h, and hold for 7.5h.
[0175] Total crystallization time: 18 hours.
[0176] Step 3, solid-liquid separation: same as in Example 1.
[0177] Step 4, PF5 gas phase purification: Same as in Example 1, 15℃, 0.1MPa gauge pressure, 2h.
[0178] Step 5, Drying: Same as in Example 1.
[0179] This comparative example combines ultrasound-assisted crystallization with PF5 purification. Although this approach introduces ultrasound to improve nucleation and increase PF5 purification on the basis of cryogenic crystallization, the mass transfer deterioration caused by high viscosity under cryogenic conditions and the LiF coating problem cannot be fundamentally solved by ultrasound and PF5 purification.
[0180] The lithium hexafluorophosphate product in this comparative example has a purity of 99.92%, a free acid content of 24.8 ppm, an insoluble matter content of 276 ppm, a moisture content of 8.8 ppm, a D50 of 148 μm, and a yield of 82.1%.
[0181] Performance testing methods:
[0182] Purity determination of lithium hexafluorophosphate: The gravimetric method is used. The sample is dissolved in anhydrous dimethyl carbonate, and the PF6- content is titrated with silver nitrate standard solution. The content of metal impurities is determined by ICP-OES, and the purity is calculated by comprehensive analysis.
[0183] Determination of free acid content: Performed according to GB / T 19282-2014, the sample is dissolved in ice water and titrated with sodium hydroxide standard solution to the phenolphthalein endpoint, and the result is converted to HF content.
[0184] Determination of insoluble content: Dissolve 10g of sample in 100mL of anhydrous dimethyl carbonate, filter through a 0.2μm polytetrafluoroethylene filter membrane, wash the filter residue three times with anhydrous dimethyl carbonate, dry and weigh, and calculate the mass fraction of insoluble matter.
[0185] Moisture content determination: performed according to GB / T 6283-2008 Karl Fischer method, using a coulometric Karl Fischer moisture analyzer with an accuracy of 0.1 ppm.
[0186] Particle size D50 determination: The volume median diameter D50 was determined using a Malvern Mastersizer 3000 laser particle size analyzer with anhydrous dimethyl carbonate as the dispersion medium.
[0187] Yield calculation: The actual mass of the product is divided by the theoretical mass of LiPF6 based on the amount of LiF fed, expressed as a percentage.
[0188] Test results:
[0189] Table 1. Performance test results of lithium hexafluorophosphate products:
[0190] Sample number purity / % Free acid / ppm Insoluble matter / ppm Moisture / ppm D50 / μm Yield / % Crystallization time / h Example 1 99.96 12.3 137 5.8 155 91.2 5.6 Example 2 99.97 9.5 105 5.2 138 92.6 4.5 Example 3 99.94 15.1 168 7.3 172 89.8 6.0 Example 4 99.96 12.8 143 6.1 148 91.8 5.6 Example 5 99.97 10.1 95 5.4 158 92.1 5.0 Comparative Example 1 99.82 85.7 1082 16.3 248 78.1 28.0 Comparative Example 2 99.88 35.2 462 10.5 185 82.3 14.0 Comparative Example 3 99.84 53.8 645 12.7 42 79.8 3.5 Comparative Example 4 99.91 27.4 308 9.2 228 80.6 28.0 Comparative Example 5 99.89 22.6 342 11.8 215 78.5 28.0 Comparative Example 6 99.85 48.3 785 11.5 35 81.0 3.0 Comparative Example 7 99.92 24.8 276 8.8 152 82.1 18.0
[0191] Test methods: Purity was determined by gravimetric method combined with ICP-OES; free acid was determined according to GB / T 19282-2014; insoluble matter was determined according to the dimethyl carbonate insoluble matter method in GB / T 19282-2014; moisture was determined according to the Karl Fischer coulometric method in GB / T 6283-2008; D50 was determined using a Malvern Mastersizer 3000 laser particle size analyzer; and yield was calculated as the ratio of actual product mass to theoretical mass.
[0192] Results analysis:
[0193] The products in Examples 1 to 5 had a purity of 99.94% to 99.97%, a free acid content of 9.5 to 15.1 ppm, an insoluble matter content of 95 to 168 ppm, and a crystallization time of 4.5 to 6.0 h.
[0194] Comparative Example 1 used conventional cryogenic cooling crystallization without PF5 purification, resulting in a purity of only 99.82%, with free acid as high as 85.7 ppm, insoluble matter as high as 1082 ppm, and a crystallization time of 28 hours.
[0195] Compared with Comparative Example 1, the purity of the examples was increased by 0.12 to 0.15 percentage points, free acid was reduced by 82% to 89%, insoluble matter was reduced by 84% to 91%, and crystallization time was shortened by 79% to 84%.
[0196] Comparative Example 2 used vacuum evaporation crystallization, but the vacuum rate was only 0.2 kPa / min, which is lower than the lower limit of 0.5 kPa / min of this invention. The crystallization time was as long as 14 hours, and the supersaturation was established too slowly, resulting in slow crystal growth. Long-term crystallization easily led to crystal aggregation, which encapsulated the LiF in the mother liquor in the aggregate. The purity was 99.88% and the insoluble matter was 462 ppm, which were significantly inferior to the example.
[0197] Comparative Example 3 had a decompression rate of 5 kPa / min, which is higher than the upper limit of 3 kPa / min in this invention. Hydrogen fluoride boiled violently, producing a large number of fine crystals with a D50 of only 42 μm. LiF was also largely coated with the crystals, and the insoluble matter was 645 ppm. This indicates that the quality of the evaporation crystallization deteriorated sharply after the decompression rate exceeded the critical range.
[0198] Comparative Example 4 used conventional cryogenic crystallization combined with the same PF5 purification conditions as Example 1, achieving a purity of 99.91% and an insoluble content of 308 ppm. Although this was an improvement over Comparative Example 1, it was far less than the 99.96% and 137 ppm of Example 1. This indicates that under the high viscosity conditions generated by cryogenic crystallization, LiF is deeply embedded inside the crystal, and PF5 purification can only remove the surface and shallow LiF, failing to reach the LiF coating inside the crystal.
[0199] Comparative Example 5 was purified using high-temperature PF5, with a purity of 99.89% and a yield of only 78.5%. This indicates that lithium hexafluorophosphate underwent partial thermal decomposition at 120℃ to generate LiF impurities, resulting in an increase in the content of insoluble matter and a decrease in yield.
[0200] Comparative Example 6 employed a combination of rapid vacuum evaporation and PF5 purification. The vacuum rate of 10 kPa / min far exceeded the range of this invention, resulting in violent evaporation of hydrogen fluoride, extremely fine crystals, and severe scaling on the crystal walls. The purity was 99.85%, the insoluble matter was 785 ppm, and the D50 was only 35 μm. Even after subsequent PF5 purification, it was still impossible to compensate for the severe LiF coating caused during the crystallization stage, and the product quality was far lower than that of this invention.
[0201] Comparative Example 7 used a combination of ultrasonic-assisted cryogenic crystallization and PF5 purification, achieving a purity of 99.92% and an insoluble content of 276 ppm. Although this was better than Comparative Example 4, it was still inferior to the Example. Furthermore, the crystallization time was 18 hours and the cooling energy consumption was high. This further proves that the deterioration of mass transfer at high viscosity under cryogenic conditions is the fundamental problem. Ultrasonic waves can only improve the uniformity of nucleation but cannot solve the problem of LiF coating caused by the deterioration of mass transfer.
[0202] Based on the above analysis, the controlled reduced pressure evaporation crystallization of the present invention achieves efficient mass transfer under medium temperature and low viscosity conditions, fundamentally avoiding LiF coating. Combined with low temperature PF5 gas phase purification to remove residual LiF and adsorbed HF from the surface, the two work synergistically to produce technical effects that exceed the sum of their individual effects.
[0203] This synergy cannot be achieved by a simple combination of existing technologies: Comparative Examples 6 and 7 show that even when evaporation crystallization or ultrasonic crystallization is combined with PF5 purification, the product quality is still significantly lower than that of the present invention if the core conditions of controlled decompression rate of 0.5 to 3 kPa / min and intermediate temperature of -5 to 5 °C are not met.
[0204] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A method for preparing lithium hexafluorophosphate, characterized in that, Includes the following steps: Step 1: Dissolve lithium fluoride in anhydrous hydrogen fluoride, and then pass phosphorus pentafluoride gas through it to react and obtain a hydrogen fluoride solution of lithium hexafluorophosphate. Step 2: Transfer the lithium hexafluorophosphate hydrogen fluoride solution obtained in Step 1 to a crystallization vessel. Under stirring conditions, slowly reduce the system pressure from atmospheric pressure to 15 to 30 kPa absolute pressure at a rate of 0.5 to 3 kPa / min, while maintaining the system temperature at -5 to 5°C, so that the hydrogen fluoride evaporates in a controlled manner and lithium hexafluorophosphate crystallizes out due to the increased concentration, thus obtaining a slurry containing lithium hexafluorophosphate crystals. Step 3: Perform solid-liquid separation on the crystal slurry obtained in Step 2, remove the mother liquor, and obtain wet lithium hexafluorophosphate crystals; Step 4: Place the wet lithium hexafluorophosphate crystals obtained in Step 3 into a purification reactor, introduce phosphorus pentafluoride gas at 10 to 25°C, maintain the system pressure at 0.05 to 0.2 MPa gauge pressure, and treat for 1 to 3 hours to allow phosphorus pentafluoride to react with the residual lithium fluoride in the wet crystals to generate lithium hexafluorophosphate, while removing hydrogen fluoride adsorbed on the crystal surface and in the gaps. Step 5: The lithium hexafluorophosphate crystals processed in Step 4 are vacuum dried under nitrogen protection to obtain the lithium hexafluorophosphate product.
2. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step one, the mass concentration of lithium fluoride in anhydrous hydrogen fluoride is 3.0 to 4.5%, the molar ratio of phosphorus pentafluoride to lithium fluoride is 1.01 to 1.05:1, the reaction temperature is -15 to -5℃, and the reaction time is 3 to 5 hours.
3. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step two, the slow decompression process is divided into three stages: the first stage reduces the pressure from atmospheric pressure to 15 to 30 kPa at a rate of 0.5 to 3 kPa / min, taking 0.5 to 3.0 h; the second stage maintains the pressure at 15 to 30 kPa and continues to evaporate hydrogen fluoride to allow crystallization to continue, taking 2 to 4 h; the third stage reduces the pressure from 15 to 30 kPa to 5 to 12 kPa at a rate of 0.3 to 1 kPa / min, while simultaneously reducing the temperature to -10 to -5 °C, taking 1 to 2 h.
4. The method for preparing lithium hexafluorophosphate as described in claim 3, characterized in that, In step two, the system temperature in the first and second stages is -3 to 3℃, and the system temperature in the third stage is -8 to -5℃.
5. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step two, the stirring speed is 50 to 150 rpm, and the evaporated hydrogen fluoride is condensed and recovered by a condenser at -30 to -20°C and recycled.
6. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step three, solid-liquid separation is achieved by nitrogen pressurized filtration at a nitrogen pressure of 0.1 to 0.3 MPa gauge pressure. The separated mother liquor is recycled back to step one for reuse.
7. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step four, the flow rate of phosphorus pentafluoride gas is 0.5 to 2.0 L / min per kilogram of wet lithium hexafluorophosphate crystals.
8. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step five, the vacuum drying temperature is 40 to 55°C, the absolute pressure is 5 to 15 kPa, the nitrogen purging flow rate is 0.5 to 2.0 L / min per kilogram of lithium hexafluorophosphate, and the drying time is 4 to 8 hours.
9. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, In step one, the purity of lithium fluoride is ≥99.95%, the D50 is 5 to 15 μm, and the moisture content is ≤10 ppm; the purity of anhydrous hydrogen fluoride is ≥99.99%, and the moisture content is ≤5 ppm.
10. The method for preparing lithium hexafluorophosphate as described in claim 1, characterized in that, After step four is completed, the purification reactor is purged with high-purity nitrogen to replace the residual phosphorus pentafluoride gas. The nitrogen purity is ≥99.999%, and the purging time is 10 to 30 minutes.
Citation Information
Patent Citations
Method for preparing lithium hexafluorophosphate
CN102910612A